Efficacy of the combination of indomethacin and methocarbamol versus indomethacin alone in patients with acute low back pain: A double-blind, randomized placebo-controlled clinical trial - Shiva Samsamshariat; Mehdi Sharifi-Sade; Shafeajafar Zoofaghari; Asieh Maghami Mehr; Ali Mohammad Sabzghabaee (Wolters Kluwer Medknow Publications, 2021)
Objective: Acute low back pain is a common ailment and causes pain and disability. Physicians often prescribe nonsteroidal anti-inflammatory drugs (NSAIDs) to treat acute low back pain; however, due attention has recently been drawn to muscle relaxants to reduce the severity of patients' daily physical dysfunction. Therefore, this study aimed to evaluate the therapeutic effect of the administration of indomethacin alone compared with methocarbamolas a muscle relaxant and indomethacin as an NSAID on the treatment of acute low back pain. Methods: The present double-blind clinical trial was performed on 64 patients with acute low back pain. The patients were categorized into two groups and received the treatments as follows. Indomethacin capsules of 25 mg every 8 h and placebo tablets every 8 h were administered in the first group (Group I). Indomethacin capsules of 25 mg every 8 h and methocarbamol tablets of 500 mg every 8 h were administered in the second group (Group I + M). Patient pain intensity and physical function based on Back Pain Function Scale (BPFS) were recorded before and 1 week after the intervention. Findings: The present study results revealed that the mean pain reduction of patients in Group I + M was significantly higher than that of Group I (3.66 ± 3.17 vs. 1.84 ± 1.53; P < 0.001). Moreover, the mean BPFS increase in Group I + M was significantly higher than that of Group I (19.44 ± 8.66 vs. 4.75 ± 4.35; P < 0.001). Conclusion: According to the results of the present study, concomitant administration of indomethacin and methocarbamol can be more effective in reducing pain intensity and improving the patient's physical function (or performance).